Re-imagining suburbia, feeling the future: Reflections on collaborative ethnographic filmmaking - Nikitina-Li, Jess (The Australian journal of anthropology, 2025)
Amalgam: On Feeling the Future is a visual anthropology project that culminated in a three-part ethnographic film series created in close collaboration with three artists living in the South-East suburbs of Naarm (Melbourne). Grounded in feminist and decolonial methodologies, and drawing from a lineage of POC (People of Colour) and Indigenous ethnographic filmmaking, Amalgam explores how art practice mediates diasporic belonging, identity, and agency for young POC (People of Colour). Drawing on concepts of assemblages and relational knowledge production, it positions filmmaking as both method and praxis—rejecting extractive modes of representation to instead embrace co-creation, collaboration, shared authority, and the privileging of process over product. Through this, Amalgam responds to the neoliberal ‘arts-washing’ and multiculturalism that proliferates arts and cultural activity in contemporary neighbourhoods. This paper reflects on the methodological implications of the project, specifically the way artistic practice—both represented in the films and enacted through their making—becomes a tool through which to negotiate identity, collectivity, and power.